Investment banking : valuation, leveraged buyouts, and mergers & acquisitions /: valuation, leveraged buyouts, and mergers & acquisitions. ([2013]) - Rosenbaum, Joshua, 1971-; Pearl, Joshua, 1981-
No abstract available